Co stabilized metallic 1Td MoS2 monolayers: Bottom-up synthesis and enhanced capacitance with ultra-long cycling stability. (March 2018) - Li, Xiaomin; Qian, Tianyue; Zai, Jiantao; He, Kai; Feng, Zhenxing; Qian, Xuefeng
Abstract: Metallic 1T layered disulfides ultrathin layers fabricated by the chemical exfoliation of 2H bulk via "top-down" method are highly attractive for energy storage because of their special metallic characteristics. However, the spontaneous transformation of 1T phase to the thermodynamically stable 2H phase is detrimental to electrochemical performance. In contrast to alkali metals, transition metals can efficiently stabilize 1T layered disulfides due to their stronger ionic potential and polarizability. Herein, Co stabilized metallic 1T MoS2 monolayers with largely distorted structure (1Td CoMoS2 ) are designed and synthesized via a "bottom-up" method, in which Co exists on the surface of SMoS monolayers via CoS bonds, rather than substituting Mo. Its unique structure endows the improved thermal stability and higher conductivity over pristine 1T MoS2, and the obtained materials exhibit an enhanced specific capacitance of 454 F g −1 (∼100 F g −1 of pristine 1T MoS2 ) at 0.5 A g −1 and a long cyclic stability with the capacitance retention of approximately 100% even after 25, 000 cycles at 10 A g −1 . Graphical abstract: Highlights: Metallic 1Td CoMoS2 monolayers were synthesized via a one pot bottom-up process. Co exists on the surface of MoS2 layer via CoS bonds, rather than substituting Mo. CoS bonds can prevent the transition from 1T to 2H, and enhance the conductivity. 1T CoMoS2 exhibit a capacitance of 454 F g −1 even after 25000 cycles at 10 A g −1 .